ON AN INEQUALITY AND A MEAN VALUE - Malešević, Jovan V. (Matematichki Bilten, 2003)
Using the papers [1] and [2] the inequality (1) is given and the author indicates the application of the given inequality on two particular cases. In the context of one of these particular cases we discovered a mean \(M(a,b)\) on the segment \([a,b]\) labeled as \(H(a,b) < M(a,b) < G(a,b)\), together with a geometric interpretation which is given, according to paper [3], by the relation \(M = H(A,H)\).